2022
DOI: 10.1371/journal.pone.0266526
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous microorganisms offset the benefits of growth and nutrition regulated by inoculated arbuscular mycorrhizal fungi for four pioneer herbs in karst soil

Abstract: Arbuscular mycorrhizal (AM) fungi, as beneficial soil microorganisms, inevitably interact with indigenous microorganisms, regulating plant growth and nutrient utilization in natural habitats. However, how indigenous microorganisms affect the benefits of growth and nutrition regulated by inoculated AM fungi for plants in karst ecosystem habitats remains unclear today. In this experiment, the Gramineae species Setaria viridis vs. Arthraxon hispidus and the Compositae species Bidens pilosa vs. Bidens tripartita e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Bidens pilosa L. is an annual herb of the Asteraceae and is widely distributed in the karst areas of southwest China (Li et al, 2021). B. pilosa is the typical pioneer succession species of karst vegetation documented by our field surveys, and our previous found that it has a high rate of mycorrhizal colonization (He et al, 2019;Han et al, 2020;Sun et al, 2022). Therefore, B. pilosa was selected as the plant material in this study.…”
Section: Plant Materialsmentioning
confidence: 97%
“…Bidens pilosa L. is an annual herb of the Asteraceae and is widely distributed in the karst areas of southwest China (Li et al, 2021). B. pilosa is the typical pioneer succession species of karst vegetation documented by our field surveys, and our previous found that it has a high rate of mycorrhizal colonization (He et al, 2019;Han et al, 2020;Sun et al, 2022). Therefore, B. pilosa was selected as the plant material in this study.…”
Section: Plant Materialsmentioning
confidence: 97%